Coping with Disruption using Social Media Marketing: A Full Throttle - Guillen Jr, Nelson B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This review expands our insights into how micro, small, and medium enterprises or MSMEs cope with disruption in Metro Manila in the Philippines using social media marketing. COVID-19 accelerated certain processes forcing local businesses to embrace digital marketing transformation. Thus, it enables local businesses to intensify their social media marketing (SMM) efforts to remain relevant due to a series of lockdowns and government-initiated restrictions. Based on the systematic review, the researcher proposes a conceptual framework to answer the question: How can MSMEs cope with disruption through social media marketing to attain positive brand equity? The proposed conceptual framework looked into synonymous themes such as marketing competencies (MC), omnichannel strategies (OC), and brand equity (BE). Within the process, MSMEs can optimize their social media marketing strategies as a springboard to reimagine the new normal with significance on how the business would aggrandize its resources. Moreover, as of October 2021, the entire nation has entered the post-pandemic period, making this study pertinent for local enterprises. Indeed, MSMEs attempt to bounce back from a two-year incubus.